Muscle PGC-1α modulates satellite cell number and proliferation by remodeling the stem cell niche. Issue 1 (December 2016) - Dinulovic, Ivana; Furrer, Regula; Beer, Markus; Ferry, Arnaud; Cardel, Bettina; Handschin, Christoph
Abstract Background The myogenic capacity of satellite cells (SCs), adult muscle stem cells, is influenced by aging, exercise, and other factors. In skeletal muscle, the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is a key regulator of oxidative metabolism and endurance training adaptation. However, a link between PGC-1α and SC behavior remains unexplored. Methods We have now studied SC function in a PGC-1α fiber-specific gain-of-function animal model. Results In surprising contrast to bona fide exercise, muscle-specific PGC-1α transgenic mice have lower SC numbers. Nevertheless, SCs from these mice have a higher propensity for activation and proliferation. Intriguingly, muscle PGC-1α triggers a remodeling of the SC niche by altering the extracellular matrix composition, including the levels of fibronectin, which affects the proliferative output of SCs. Conclusions Taken together, PGC-1α indirectly affects SC plasticity in skeletal muscle and thereby might contribute to improved SC activation in exercise.